2020
DOI: 10.1186/s12886-020-01385-1
|View full text |Cite
|
Sign up to set email alerts
|

Corneal thickness and endothelial morphology in Normal Thai eyes

Abstract: Background: This study aimed to determine the influence of age on central corneal thickness and corneal endothelial morphology as well as to identify the relationship between them in normal Thai eyes. Methods: Non-contact specular microscopy was performed in volunteers stratified into seven age groups ranging from 11 to 88 years. The corneal endothelial parameters studied included central corneal thickness (CCT), endothelial cell density (ECD), coefficient of variation in cell size (CV), cell area (CA) and per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
6
17
2
Order By: Relevance
“…In accordance with our results, El-Sayyad et al [33] and Halawa [34] found that the cornea of aged rats exhibited atrophied epithelium with small dark nuclei, hyalinization of the stromal collagen fibrils, keratocystic loss and degeneration of the lining endothelium. In contrast to our results, Tananuvat and Khumchoo [36] demonstrated that there is a significant inverse correlation between age and central corneal thickness in humans.…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with our results, El-Sayyad et al [33] and Halawa [34] found that the cornea of aged rats exhibited atrophied epithelium with small dark nuclei, hyalinization of the stromal collagen fibrils, keratocystic loss and degeneration of the lining endothelium. In contrast to our results, Tananuvat and Khumchoo [36] demonstrated that there is a significant inverse correlation between age and central corneal thickness in humans.…”
Section: Discussioncontrasting
confidence: 99%
“…Outside Africa, cross-sectional studies estimated that CCT decayed by 0.28 μm/year among 12–60 years old Turkish [ 60 ], 0.48 μm/year in 40 years and older Mongolians [ 27 ], 0.58 μm/year of age in 30 years and older Lithuanians [ 9 ], 0.5 μm/year in 6 years and older Iranians [ 61 ], 0.3 μm/year in a multiethnic population including Caucasians, Chinese, Japanese, Hispanics, Filipinos, and African Americans aged in average 67.3 years [ 62 ], and 0.3 μm/year and 0.5 μm/year in 50 years and older Chinese [ 63 ]. Regression analysis suggested that CECD decayed at a rate of 8.3 cells/mm 2 or 0.30% per year of age in the present study, which is comparable to 0.27–0.30% reported in Pakistani [ 26 ], Chinese [ 32 ], and Indians [ 36 ]; higher than 0.23 and 0.25% per year found in Thais [ 11 ] and Japanese [ 64 ], respectively, but lower than 0.5–0.6% estimated in Chinese [ 65 , 66 ], New Zealanders [ 67 ] and Americans [ 68 ].…”
Section: Discussionsupporting
confidence: 82%
“…This is unlike previous studies where comparison of CCT and/or CECD with other studies were made without considering the difference in age across studies. When we restricted the comparison to previous studies whose whole populations' age range was comparable to ours, central cornea in this Congolese sample was as thick as measured in Pakistanis [26] and Mongolians [27], but thinner than reported in Thais [11], Cameroonians [15], Iranians [28], Spaniards [29], and Turkish [30]. Among these studies four of them also reported the morphometry of endothelial cells [11,26,29,30]; and measured lower CECD than we found.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations